(untitled) (Global Journal of Human-Social Science, 2016)
The city of Istanbul historically witnessed many cases of violence The nature of the violence changed with times and its aggravation had seasons while some violence was almost always present in some form or another Being a cosmopolitan urban center violence seems to be one of the additives in the city s very essence and nature